1974
DOI: 10.2105/ajph.64.5.459
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an 18 months' physical training program for middle-aged men and its effect on physical fitness.

Abstract: An exercise program to prevent coronary heart disease in middle-aged men is described and its effects on the subjects' physical fitness are reported. MethodsA feasibility study on physical activity intervention for coronary heart disease prevention among middle-aged sedentary men displaying relatively high values in selected coronary heart disease (CHD) "risk factors" has been performed in Helsinki, Finland. CHD risk status, clinical contraindications, motivation, and habitual physical activity were the criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Previous research reports CRF’s significant protective effects on all-cause mortality, 13,14 cancer-related mortality, 15 diabetes incidence, 16 CHD incidence, 17 and CHD mortality. 8,18,19 Barlow et al 20 reported that a 1-unit metabolic equivalent of task (MET) increase in baseline CRF resulted in an 18% decrease in CVD mortality in FRS-classified “low-risk” adults over a 30-year follow-up period.…”
mentioning
confidence: 98%
“…Previous research reports CRF’s significant protective effects on all-cause mortality, 13,14 cancer-related mortality, 15 diabetes incidence, 16 CHD incidence, 17 and CHD mortality. 8,18,19 Barlow et al 20 reported that a 1-unit metabolic equivalent of task (MET) increase in baseline CRF resulted in an 18% decrease in CVD mortality in FRS-classified “low-risk” adults over a 30-year follow-up period.…”
mentioning
confidence: 98%
“…However, as in many voluntary therapeutic settings, recidivism presents a major impediment to effective treatment. Adult fitness programs have typically reported adherence rates of only 40-65% (Bruce, Frederick, Bruce, & Fisher, 1976;Massie & Shephard, 1971;Morgan, 1977a;Oja, Teraslinna, Partanen, & Karava, 1975;Oldridge, 1977aOldridge, , 1977bSidney & Shephard, 1976), indicating a substantial dropout percentage among those who volunteer to enter an exercise program. Therefore, from a practical as well as a theoretical standpoint, there exists a need to determine what factors are most likely to contribute to adherence to such programs-a problem that is analogous in many respects to the problem of ensuring patient compliance in many medical treatment programs.…”
mentioning
confidence: 99%
“…the sporadic attendance in these programs (cf., Oja, Teraslinn, Partanen, & Karava, 1974;Sime, Whipple, Stamler, & Berkson, 1976). The major question remains, how can people be motivated to participate regularly in physical fitness activities?…”
mentioning
confidence: 99%